2011
DOI: 10.1093/fampra/cmr045
|View full text |Cite
|
Sign up to set email alerts
|

Widespread use of pure and impure placebo interventions by GPs in Germany

Abstract: To collect data on the use of placebo interventions by GPs in Germany.Methods. A questionnaire was mailed to 400 randomly selected GPs in Bavaria. Non-responders were reminded by telephone after 4 weeks and were given a second copy of the questionnaire after a further 3 weeks. Results. In all, 208 completed questionnaires were returned. The majority of GPs (88%) have used a placebo at least once in their practice; 45% have used pure placebos, such as saline injections and sugar pills, at least once last year; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(101 citation statements)
references
References 15 publications
5
90
1
5
Order By: Relevance
“…[5] The latest survey of placebo use was published after the systematic review and found 45% of German GPs had used pure placebos and 76% had used impure placebos in the last year. [12] Hence the results of our UK survey are internationally consistent.…”
Section: Strengths and Limitationssupporting
confidence: 62%
See 3 more Smart Citations
“…[5] The latest survey of placebo use was published after the systematic review and found 45% of German GPs had used pure placebos and 76% had used impure placebos in the last year. [12] Hence the results of our UK survey are internationally consistent.…”
Section: Strengths and Limitationssupporting
confidence: 62%
“…[4,7,10,11,12] Pure placebos are interventions such as sugar pills (which are available commercially [31]) or saline injections without direct pharmacologically active ingredients for the condition being treated. Impure placebos are substances, interventions or 'therapeutic' methods which have known pharmacological, clinical or physical value for some ailments but lack specific therapeutic effects or value for the condition for which they have been prescribed.…”
Section: Defining Pure and Impure Placebosmentioning
confidence: 99%
See 2 more Smart Citations
“…The basic paradox with the term "placebo effect" is that, by definition, a placebo -an inert substance or procedure -cannot elicit an effect [5,6]. A further problem arises if "placebo" is understood as an upper level category that is divided into two lower level categories, "pure" and "impure" placebos [7,8]. In several surveys these two categories were taken for granted; yet their problematic nature has also been acknowledged: "What is considered to be an impure placebo varies considerably among studies and it is unclear and subjective when an intervention is a placebo or an active or effective intervention.…”
Section: Introductionmentioning
confidence: 99%